A User Cost Approach to New Automobile Purchases - Wykoff, Frank C. (Review of Economic Studies, 1973)
Journal Article A User Cost Approach to New Automobile Purchases Get access Frank C. Wykoff Frank C. Wykoff Pomona College Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 3, July 1973, Pages 377–390, https://doi.org/10.2307/2296457 Published: 01 July 1973